(untitled) (Archives of Clinical and Medical Case Reports, 2019)
This report describes a male with insulin pump-treated type 1 diabetes mellitus admitted with diabetic ketoacidosis after a gastroenteritis while following a very low carbohydrate diet. Combining such diet, using an insulin pump and suffering a gastroenteritis may represent an increased risk of diabetic ketoacidose.